The Role of Archive Management in Supporting Licensing Services at the Dpmptsp of East Java Province - Maria Sherena Agustine; Bayu Priambodo (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Archive management is an important part of the implementation of government administration, especially in supporting fast, accurate, and accountable licensing services. The East Java Province Investment and One-Stop Integrated Service Agency (DPMPTSP) as the agency that organizes licensing services produces a high volume of archives, thus requiring orderly archive management in accordance with archival principles. This study aims to analyze the role of archive management in supporting licensing services at the DPMPTSP of East Java Province. This study uses a qualitative approach with a descriptive research type and a case study strategy. Data were obtained through observation, interviews, and documentation studies during the implementation of internship activities. The results show that archive management plays an important role in supporting the speed of service through easy retrieval of archives, increasing service accuracy through the accuracy and consistency of licensing data, and strengthening service accountability through the availability of archives as administrative and legal evidence. However, archive management at the DPMPTSP of East Java Province still faces obstacles, especially related to limited human resources for archives, a filing system that is not yet fully uniform, and supporting facilities and infrastructure. Therefore, continuous strengthening of archives management is necessary to support optimal licensing service quality